High fatigue resistance of a photochromic dithienylethene embedded into the pores of a metal–organic framework (MOF). Issue 12 (26th November 2020) - Schwartz, Heidi A.; Laurenzen, Hannah; Kerschbaumer, Samuel; Werker, Melanie; Olthof, Selina; Kopacka, Holger; Huppertz, Hubert; Meerholz, Klaus; Ruschewitz, Uwe
Abstract : The incorporation of photochromic dyes into porous metal–organic frameworks (MOFs) is an attractive way to transfer the photochromic properties of the dye to a solid crystalline material. Abstract : The incorporation of photochromic dyes into porous metal–organic frameworks (MOFs) is an attractive way to transfer the photochromic properties of the dye to a solid crystalline material. In this work, the well-known P-type chromophore 1, 2-bis[2-methylbenzo[ b ]thiophen-3-yl]-3, 3, 4, 4, 5, 5-hexafluoro-1-cyclopentene (DTE) is embedded in three different MOFs, namely MOF-5, MIL-68(In), and MIL-68(Ga). The successful filling of the MOF pores with the DTE guest was proven by X-ray powder diffraction, while the amount of the embedded guest molecules was investigated by X-ray photoelectron spectroscopy (XPS), liquid-state NMR and thermal analysis (DSC/TGA). The measurements reveal an unexpectedly low filling of the MOF pores with the DTE guest ( e.g. in MOF-5 only every fifth MOF pore is filled with a guest molecule) as well as an inhomogeneous loading throughout the material. Reflection spectra clearly show the transitions of the colourless open-ring and the coloured closed-ring forms of the DTE guest upon UV ( λ = 365 nm), blue ( λ = 405 nm) and green ( λ = 535 nm) light exposure, where the latter is usually suppressed in crystalline DTE. Remarkably, no fatigue after ten switching cycles was observed and a high thermal stability of the coloured closed-ring form (at 50 °C for 1 h) was achieved.